Macrophage-Targeted Therapeutics for Metabolic Disease. (June 2018) - Peterson, Kristin R.; Cottam, Matthew A.; Kennedy, Arion J.; Hasty, Alyssa H.
Abstract : Macrophages are cells of the innate immune system that are resident in all tissues, including metabolic organs such as the liver and adipose tissue (AT). Because of their phenotypic flexibility, they play beneficial roles in tissue homeostasis, but they also contribute to the progression of metabolic disease. Thus, they are ideal therapeutic targets for diseases such as insulin resistance (IR), nonalcoholic fatty liver disease (NAFLD), and atherosclerosis. Recently, discoveries in the area of drug delivery have facilitated phenotype-specific targeting of macrophages. In this review we discuss advances in potential therapeutics for metabolic diseases via macrophage-specific delivery. We highlight micro- and nanoparticles, liposomes, and oligopeptide complexes, and how they can be used to alter macrophage phenotype for a more metabolically favorable tissue environment. Highlights: Macrophages are complex cells with phenotypic plasticity to meet ever-changing tissue environment demands and their phagocytic properties make them ideal therapeutic targets. Depletion of all macrophages via clodronate-loaded liposomes was the historical way to experimentally alter the inflammation associated with macrophage activation in metabolic tissues such as liver and adipose. Recent advances allow more directed targeting with regard to both specific macrophage subpopulations (M1 like vs M2 like) and modulation of certain functions (gene targeted knockdown). Receptor-mediated endocytosis can be utilized to facilitate transport of therapeutic vectors with high specificity. Therapeutics that modulate inflammatory gene expression can be transported in nanoparticle and oligopeptide vectors.